Churchill the unexpected hero - Addison, Paul, 1943- (Oxford ; New York : Oxford University Press, 2005)
"In this incisive biography, Paul Addison examines both the life of the most iconic figure in twentieth-century Bristish history, and the battle over his reputation, which continues to this day."--Jacket.
The youngest man in Europe, 1874-1901 -- The renegade, 1901-1911 -- The Lilliput Napoleon, 1911-1915 -- The Winstonburg line, 1915-1924 -- Respectability won and lost, 1924-1939 -- The making of a hero, 1939-1945 -- Climbing Olympus, 1945-1965 -- Churchill past and present.
Includes bibliographical references (p. 275-285) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2023. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Churchill, Winston, -- 1874-1965.; Prime ministers -- Great Britain -- Biography; Great Britain -- Politics and government -- 20th century; Electronic books